Agency Business Transformation Based on Digital Platforms: Entrepreneurship Training and Career Readiness within LP3I - Batubara, Supina; Fanny (Jurnal Pengabdian Masyarakat Berdampak, 2026)
The rapid shift toward a digital economy often leaves final year students and university staff unprepared to navigate modern job markets or seize independent business opportunities. This community service program, held on June 6, 2026, aims to empower the civitas akademika at LP3I by equipping them with practical digital career skills and exploring innovative, platform based entrepreneurship avenues. Using an immersive Action Management Training (AMT) workshop framework, the program combined interactive mentoring, a hands on review of digital portfolio structures, and an engaging Business Opportunity Presentation (BOP). A total of 55 participants including students, lecturers, and administrative staff actively engaged in this collaborative session. Program success was evaluated using descriptive capability mapping before and after the event. The results reveal a tangible 35% improvement in participants' ability to construct modern, automated applicant tracking system (ATS) friendly resumes. Furthermore, their understanding of digital entrepreneurship and financial risk management grew by 40%. Beyond skill acquisition, the workshop created direct economic value, inspiring 25% of the participants to formally join the digital agency network as independent business partners. This collective effort successfully bridges the gap between academic theory and real-world industrial application.